Fierro, C. (2016). Teaching the history of psychology and training of psychologists. Current developments and debates in Argentina and the world. Arequipa: Sociedad Peruana de Historia de la Psicología/Adrus, 338 pp. - Arias-Gallegos, Walter Lizandro (2017)
No presenta resumen.